Catalpol as a Component of Rehmannia glutinosa Protects Spinal Cord Injury by Inhibiting Endoplasmic Reticulum Stress-Mediated Neuronal Apoptosis - Huang, Zhiyang; Gong, Jiahong; Lin, Wen; Feng, Zhiyi; Ma, Yirou; Tu, Yurong; Cai, Xiong; Liu, Jianhua; Lv, Chang; Lv, Xinru; Wu, Qiuji; Lu, Wenjie; et al. (Frontiers in Pharmacology, 2022)
Disturbance of the internal environment in the spinal cord after spinal cord injury (SCI) is an important cause of the massive death of neurons in the injury area and one of the major problems that lead to the difficult recovery of motor function in patients. Rehmannia glutinosa, a famous traditional Chinese medicine, is commonly used in neurodegenerative diseases, whereas an iridoid glycoside extract of catalpol (CAT), with antioxidant, antiapoptotic, and neuroprotective pharmacological effects. However, the neuroprotective and anti-apoptosis mechanism of CAT in SCI remains unclear. In our study, we found that CAT has a restorative effect on the lower limb motor function of rats with SCI by establishing a rat model of SCI and treating CAT gavage for 30 days. Our study further found that CAT has the effect of inhibiting apoptosis and protecting neurons, and the action pathway may reduce endoplasmic reticulum (ER) stress by inhibiting CHOP and GRP78 expression and then reduce apoptosis and protect neurons through the Caspase3/Bax/Bcl-2 pathway. In conclusion, we demonstrated that CAT can treat SCI by inhibiting ER stress-mediated neuronal apoptosis and has the potential to be a clinical drug for the treatment of SCI.